Effect of Patient Demographics and Tracheostomy Timing and Technique on Patient Survival. (15th August 2020) - Park, Christopher; Bahethi, Rohini; Yang, Anthony; Gray, Mingyang; Wong, Kevin; Courey, Mark
Abstract : Objectives: The ideal timing and technique of tracheostomy vary among patients and may impact outcomes. We aim to examine the association between tracheostomy timing, placement technique, and patient demographics on survival. Study Design: Retrospective cohort study. Methods: A retrospective review was performed for all patients who underwent tracheostomy in 2016 and 2017 at one urban academic tertiary‐care hospital. Kaplan–Meier curves were created based on combinations of tracheostomy timing and technique (early percutaneous, early non‐percutaneous, late percutaneous, and late non‐percutaneous). Cox proportional hazard models were used to determine multivariable effects of timing, technique, and other demographic factors. Primary outcome measures were tracheostomy‐related mortality and overall survival. Secondary outcomes were in‐hospital, 30‐day, and 90‐day mortality. Results: Our study included 523 patients. There were six tracheostomy‐related deaths, with hemorrhage and tracheoesophageal fistula being the most common causes. Tracheostomy timing and technique combinations were not associated with differences in all‐cause mortality or survival following discharge. Cox proportional hazard models showed that Charlson Comorbidity Index (CCI) and unknown partner status were associated with a decrease in survival ( P  < .01 and P  = .05, respectively). Additionally, patient age, gender, race, CCI, and body mass index were not independently associated with changes in survival. Conclusion: Late and non‐percutaneous tracheostomies were associated with more tracheostomy‐related deaths, but timing and technique were not associated with differences in patient survival. Multiple regression analysis showed that increased patient comorbidities, measured via CCI, and unknown partner status were independently associated with decreased survival. Proceduralists should discuss timing, technique, and patient social factors together with the medical care team when constructing plans for postdischarge management. Level of Evidence: 4 Laryngoscope, 131:1468–1473, 2021